Ly9 (SLAMF3) receptor differentially regulates iNKT cell development and activation in mice. Issue 1 (7th November 2017) - Cuenca, Marta; Puñet‐Ortiz, Joan; Ruart, Maria; Terhorst, Cox; Engel, Pablo
Abstract: Invariant natural killer T (iNKT) cells develop into three subsets (NKT1, NKT2, and NKT17) expressing a distinct transcription factor profile, which regulates cytokine secretion upon activation. iNKT cell development in the thymus is modulated by signaling lymphocytic activation molecule family (SLAMF) receptors. In contrast to other SLAMF members, Ly9 (SLAMF3) is a non‐redundant negative regulator of iNKT cell development. Here, we show that Ly9 influences iNKT cell lineage differentiation. Ly9 ‐deficient mice on a BALB/c background contained a significantly expanded population of thymic NKT2 cells, while NKT1 cells were nearly absent in BALB/c. Ly9 −/− thymus. Conversely, the number of peripheral NKT1 cells in BALB/c. Ly9 −/− mice was comparable to that in wild‐type mice, indicating that the homeostasis of the different iNKT cell subsets may have distinct requirements depending on their tissue localization. Importantly, Ly9 absence also promoted NKT2 cell differentiation in the NKT1‐skewed C57BL/6 background. Furthermore, treatment of wild‐type mice with an agonistic monoclonal antibody directed against Ly9 impaired IL‐4 and IFN‐γ production and reduced by half the number of spleen iNKT cells, with a significant decrease in the proportion of NKT2 cells. Thus, anti‐Ly9 targeting could represent a novel therapeutic approach to modulate iNKT cell numbers and activation. Abstract : Ly9 (SLAMF3) cell‐surface receptor is a negative regulator of iNKT development. Here we show that Ly9 absence favors the differentiation of NKT2 cells over NKT1 cells, leading to increased numbers of innate CD8 + cells. Furthermore, in vivo targeting of Ly9 with monoclonal antibodies diminishes splenic NKT cell numbers and activation.